Effect of aluminum Tripolyphosphate on pitting initiation on carbon steel in chloride contaminated concrete pore solution. Issue 5 (2nd September 2019) - Lu, Xiangyu; Zhang, Leyuan; Feng, Xingguo; Chen, D.; Zuo, Yu
Abstract : Purpose: Aluminum tripolyphosphate was used as a corrosion inhibitor in a simulated concrete pore solution. For studies of the inhibition mechanism of aluminum tripolyphosphate on the carbon steel, its influence on the pitting initiation on the carbon steel in a Cl − containing pore solution were investigated. Design/methodology/approach: Potentiodynamic polarization curves, Mott–Schottky plots and potentiostatic polarization of the carbon steel in the pore solution with different content of aluminum tripolyphosphate were measured, as well as the optical micrographs of pitting on the carbon steel was observed. Findings: The metastable pitting potential and the stable pitting potential increased, while the donor density and the flat band potential decreased with the concentration of aluminum tripolyphosphate in solution. Furthermore, the initiation of pitting was suppressed, as well as the transition from metastable to stable pitting was hindered by the aluminum tripolyphosphate. The scale parameter (a), in the extreme distribution of the maximum current peak, could be used to predict the transition from metastable to stable pitting. Originality/value: The inhibition mechanism of aluminum tripolyphosphate on carbon steel in pore solution was revealed. It suppresses the initiation of pitting and hinders the transition from metastable to stable pitting. Furthermore, a parameter defined as the scale parameter (a) in the extreme distribution of the maximum current peak was introduced to predict the transition from metastable to stable pitting.